Paradigms in Modern Russian and Foreign Linguistics: Nature, Dynamics, and Philosophical Grounds - T. V. Dubrovskaya (Научный диалог, 2019)
The author discusses the category of paradigm introduced by Thomas Kuhn, systematizes and summarizes the principal claims advanced by home and foreign scholars, reveals the most common trends in understanding paradigms in modern humanities, specifically in linguistics. It is demonstrated that the category of paradigm remains popular, but it has undergone some transformations. Considering the review, it can be assumed that the strict understanding of paradigms as incompatible model problems and solutions to them is being replaced by more flexible statements about a greater or lesser importance of a given paradigm over a specific period. Scholars admit the possibility to return to old research problems and tackle them at a higher level, focus on building a universal paradigm that would incorporate various directions of studies and views of language. The author characterizes paradigm arguments in Western research methodology as constructed on the basis of different philosophical approaches to knowledge (admitting or rejecting the possibility to learn the objective truth). It is shown that the methodological compromise has resulted in ‘compatibility principle’, mixed-method research, and a combination of qualitative and quantitative research in humanities, including linguistics.